2010
DOI: 10.1117/1.3316378
|View full text |Cite
|
Sign up to set email alerts
|

Use of optical tweezers to probe epithelial mechanosensation

Abstract: Abstract. Cellular mechanosensation mechanisms have been implicated in a variety of disease states. Specifically in renal tubules, the primary cilium and associated mechanosensitive ion channels are hypothesized to play a role in water and salt homeostasis, with relevant disease states including polycystic kidney disease and hypertension. Previous experiments investigating ciliary-mediated cellular mechanosensation have used either fluid flow chambers or micropipetting to elicit a biological response. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Controlled extension of silicone [10] or hydrogel [11] substrates can mimic ECM stretching in vivo. More targeted methods of physically perturbing cells include the use of optical tweezers [12], atomic force microscopy [13], and magnetic twisting cytometry [14]. Some of these tools have also been used to assess “inside-out” mechanosensing by measuring the force with which a cell pulls on its extracellular environment [15].…”
Section: Controlling the Physical Microenvironment Of The Cellmentioning
confidence: 99%
“…Controlled extension of silicone [10] or hydrogel [11] substrates can mimic ECM stretching in vivo. More targeted methods of physically perturbing cells include the use of optical tweezers [12], atomic force microscopy [13], and magnetic twisting cytometry [14]. Some of these tools have also been used to assess “inside-out” mechanosensing by measuring the force with which a cell pulls on its extracellular environment [15].…”
Section: Controlling the Physical Microenvironment Of The Cellmentioning
confidence: 99%
“…129 Third, Using laser tweezers, Resnick et al . 128 applied mechanical forces directly to the apical surface of MDCK cells and found a null intracellular Ca 2+ response indicating that the apical membrane does not participate in mechanotransduction. Collectively, these results strongly suggest that primary cilia are the mechanosensing organelle in the CCD.…”
Section: In Vivo In Situ and Cell Culture Experiments To Validate Thmentioning
confidence: 99%
“…Long considered vestigial structures, recent work has conclusively demonstrated that the primary cilium is in fact a calcium signaling center for the cell [1] organizing a large number of signaling pathways. Demonstrations that bending a primary cilium via fluid flow [2], optical tweezers [3], or micropipette [4] initiates intracellular calcium release imply that physiologically, the primary cilium is a flow sensor. However, the biological significance of this function remains unclear.…”
Section: Introductionmentioning
confidence: 99%